2011
DOI: 10.1177/014556131109000819
|View full text |Cite
|
Sign up to set email alerts
|

Return to Contact Sports following Infectious Mononucleosis: The Role of Serial Ultrasonography

Abstract: Splenic rupture is a rare but potentially fatal complication of infectious mononucleosis. Athletes returning to contact sports following infectious mononucleosis are at potential risk of splenic rupture secondary to abdominal trauma. No clear consensus exists as to when it is safe to allow these athletes return to contact sports. Suggested periods of abstinence have ranged from 2 weeks to 6 months. We outline our experiences with the use of abdominal ultrasonography at 1 month aft er the diagnosis of infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…False-positive labeling of a patient as having splenomegaly can lead to medical tests that invariably will be negative, causing unnecessary anxiety to the patient as well as health care expenditure. Because of the potential risk of splenic rupture of an enlarged spleen, absence of splenomegaly has been mentioned as a requirement for peripheral blood stem cell donation (4,6,8,9) and as a requirement for participation in contact sports after infectious mononucleosis (5,10,11). The ability to recognize a spleen as abnormal inevitably requires generally accepted reference values.…”
Section: Volunteersmentioning
confidence: 99%
“…False-positive labeling of a patient as having splenomegaly can lead to medical tests that invariably will be negative, causing unnecessary anxiety to the patient as well as health care expenditure. Because of the potential risk of splenic rupture of an enlarged spleen, absence of splenomegaly has been mentioned as a requirement for peripheral blood stem cell donation (4,6,8,9) and as a requirement for participation in contact sports after infectious mononucleosis (5,10,11). The ability to recognize a spleen as abnormal inevitably requires generally accepted reference values.…”
Section: Volunteersmentioning
confidence: 99%
“…A recent case series provided preliminary evidence of how serial ultrasound could prove useful in this manner (51). In that study, 84% of athletes had a return of splenic size to baseline at 1-month follow-up.…”
Section: Resultsmentioning
confidence: 96%
“…There are few studies in the literature on the visceral organ dimensions of athletes in various branches. [6,[9][10][11][12][13][14] Other studies mainly aimed to create reference values in healthy adults. [8,[15][16][17][18][19][20][21][22][23][24][25][26] To our knowledge, this is the first study that has evaluated spleen, kidney and liver dimensions in the football players.…”
Section: Introductionmentioning
confidence: 99%
“…[9,23] In addition, splenomegaly (longitudinal length ≥13 cm) may be a risk factor for splenic rupture. [13] False-positive labeling of a patient as having splenomegaly can lead to conducting unnecessary medical tests and anxiety for the athletes as well as delaying for participation in contact sports activity. [6,9] In various studies, the long axis length of the spleen was reported as 10.76±1.84 cm, [24] 11.1±0.9 cm [25] and the average as 10.9 cm [23] for healthy adults.…”
mentioning
confidence: 99%